Sistem Informasi Geografis Penyebaran Mahasiswa Magang Universitas Stella Maris Sumba - Frengkianus Aprianto Kamuri; Gergorius Kopong Pati; Mitra Permata Ayu (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Geographic Information Systems (GIS) play a vital role in managing and analyzing data related to geographical locations. This research aims to develop a Geographic Information System to map the distribution of internship students at Stella Maris University, Sumba, based on their geographical locations. This system is expected to provide clearer and more detailed information regarding the distribution of internship students, making it easier for the university to plan and manage internship activities more efficiently. This system is built using web-based GIS software, with location data obtained from the university's internship management system. By utilizing GIS technology, users can easily access digital maps that show the locations of students' internships and analyze their distribution. The implementation of this system is expected to benefit students, the university, and partner companies in monitoring the progress of the internship program and ensuring its successful implementation. The advantage of this system is its ease of access and use, as well as its ability to provide more accurate and visual data. It is hoped that this system will serve as a reference for the development of similar systems in the future and contribute positively to higher education in Sumba